ANALISIS PENGARUH UKURAN PERUSAHAAN, LEVERAGE, PROFITABILITAS DAN RISIKO LIKUIDITAS TERHADAP PENGUNGKAPAN BERBASIS WEB - Amir Faisal; Vivi Julianti (Media Riset Akuntansi, Auditing & Informasi, 2020)
The purpose of this research is to examine the influence of company size, leverage, profitability and liquidity risk on web-based disclosure. Data obtained from the company's quarter financial report downloaded on the website www.idx.co.id. The sampling method used purposive sampling with criteria listed on Indonesia Stock Exchange in 2018, company included in banking sector and have an official website, the website personally belongs to the company not the parent nor the group, is not under inaccessible or under maintenance when the sampling takes place, the company issued and had not suffered net loss in the quarterly financial statement of 2018, and does not belongs to Islamic banking. Data analysis techniques used are descriptive statistics, classical assumption test, and regression test with multiple linear regression analysis using SPSS. The results showed that company size had positive effect on web based disclosure, leverage and liquidity risk had negative effect on web based disclosure, and profitability did not affect the web based disclosure.